Effects of Nitrogen Application Rate and Ratio on Lodging Resistance of Super Rice with Different Genotypes - Wu-jun ZHANG; Gang-hua LI; Yi-ming YANG; Quan LI; Jun ZHANG; Jin-you LIU; Shaohua WANG; She TANG; Yan-feng DING (Journal of Integrative Agriculture, 2014)
The objective of this study was to determine the morphology mechanism of nitrogen (N) fertilizer rates and ratio on lodging resistance through analying its effects among lodging index (LI), lodging-related morphological traits and physical strength in basal internodes by comparing japonica and indica super rice cultivars. Field experiments, with three nitrogen levels (0, 150 and 300 kg ha−1) and two ratios of basal to topdressing (8:2 and 5:5) with two super rice cultivars (Yliangyou 2 and Wuyunjing 23), were conducted in the Baolin Farm, Danyang Country, Jiangsu Province, China, in 2011 and 2012. Effects of N fertilizer rates and ratios on morphology of whole plant, morphology traits in basal internodes and culm's physical strength parameters were investigated at 20 d after full heading stage. LI of Yliangyou 2 was significant greater than that of Wuyunjing 23 due to larger bending moment by whole plant (WP) with higher plant height and gravity center height. With higher volume of N fertilizer, LI of two super rice cultivars was increased conspicuously. However, no significant effect was detected with increase of panicle fertilizer ratio. The size of breaking strength (M) in basal internodes was the key factor determining LI among N fertilizer treatments. Correlation analysis revealed that M value was positively related bending stress (BS) of Wuyunjing 23 and section modulus (Z) of Yliangyou 2, respectively. The higher N fertilizer levels induced reduction of BS of Wuyunjing 23 due to weak culm and leaf sheath plumpness status and reduced Z of Yliangyou 2 owning to small diameter and culm wall thickness, consequently, influencing their M indirectly. These results suggested that breaking strength was the key factor influencing LI with increase of N fertilizer levels. However, the lodging-related morphology mechanism was different with genotypes. Culm wall thickness and diameter in basal internodes of indica super rice and culm and leaf sheath plumpness status of japonica super rice influenced breaking strength, as well as lodging index, respectively.